EFEKTIVITAS PEMBERIAN TELUR REBUS TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Sari Ida Miharti; Maiyuliana Maiyuliana (Maternal Child Health Care, 2022)
Tanjung Gadang Health Center is one of the health centers in Sijunjung Regency which reported 128 cases of normal deliveries with perineal injuries. Mothers giving birth normally in 2021. And these cases were dominated by degree 2 perineal rupture at Tanjung Gadang Health Center in 2021. The purpose of the study was to to determine the effectiveness of giving boiled eggs on perineal wound healing in postpartum women . This research is quantitative with Quasi Experimental type with post test only non equivalent control group design . The population in this study were all postpartum mothers in the Tanjung Gadang Health Center, Sijunjung Regency as many as 30 postpartum mothers. The research was conducted in Januari 2022. The sample of this study was 30 people who were divided into 2 experimental groups. Sampling with total sampling, data were analyzed by Univariate and Bivariate. The results of the univariate analysis showed that the average wound healing score (REEDA Scale) in the group given one boiled egg a day after 7 days was 5.42 said to be slow and in the group giving two boiled eggs a day after 7 days was 3.84 it was said to be fast. The results of the bivariate analysis showed the effectiveness of giving boiled eggs on perineal wound healing in postpartum women (P value = 0.013). So, Wound healing was better in the intervention group of 2 boiled eggs/day . It is hoped that postpartum mothers will increase their knowledge and apply the consumption of boiled eggs to accelerate the healing of perineal wounds in postpartum women .  Keywords : Postpartum Mother, Perineal Wound, Boiled Egg